2021
DOI: 10.5114/ada.2021.108907
|View full text |Cite
|
Sign up to set email alerts
|

Association between biochemical hyperandrogenism parameters and modified Ferriman-Gallwey score in patients with hirsutism in Basrah (Southern Iraq)

Abstract: Introduction Hyperandrogenemia is the most frequent endocrine disorder in women causing a variety of adverse metabolic disturbances. Establishing the diagnosis of androgen overproduction has significant implications for the follow-up and treatment of patients. Aim To investigate the severity of hirsutism and its correlation with serum androgen in women with hirsutism from Basrah (Southern Iraq). Material and methods This was a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The cut-off of total Testosterone = ≤57.7 ng/dl. In group A, the total Testosterone was 79.42±17.40 and in the group, B was 79.90±15.39 8 . Total follicles in group A,=13.06±0.68 and in group B=13.33± 0.48, cut-off value = ≥12 and coinciding the study done by Wongwananuruk et al 15 .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The cut-off of total Testosterone = ≤57.7 ng/dl. In group A, the total Testosterone was 79.42±17.40 and in the group, B was 79.90±15.39 8 . Total follicles in group A,=13.06±0.68 and in group B=13.33± 0.48, cut-off value = ≥12 and coinciding the study done by Wongwananuruk et al 15 .…”
Section: Resultsmentioning
confidence: 88%
“…2) Clinical or biochemical hyperandrogenism (Ferriman-Gallwey score ≥8 or Total testosterone ≥ 50ng/dL). 3) Polycystic ovaries on ultrasound ≥12 antral follicles measuring 2-9 mm in diameter or ovarian volume >10 mL in at least 1 ovary by trans-abdominal ultrasound 8 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirsutism can be quantified by the androgen level based on the hirsutism score (Ferriman-Gallwey/modified Ferriman-Gallwey) and is the most commonly used clinical diagnostic criterion for hyperandrogenism. Relevant study has shown that the severity of hirsutism is correlated with biochemical hyperandrogenism markers, and hirsutism score has a stronger correlation with FT level, but a lesser extent to TT level ( 33 ). It is speculated that the severity of hirsutism depends mainly on the bioavailable circulating and FT.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for estimating the density of terminal hairs at nine distinct body locations is presently the (mFG) score 17 . The nine androgen-sensitive body areas include the upper lip, chin, chest, upper and lower back, upper and lower abdomen, upper arm, and thigh [14].…”
Section: Chart 1: Prevalence Ratios Of Global Pool and Different Coun...mentioning
confidence: 99%